Mesenchymal Stem Cells Functionalized Sonodynamic Treatment for Improving Therapeutic Efficacy and Compliance of Orthotopic Oral Cancer. Issue 48 (28th October 2020) - Sun, Lei; Xu, Yurui; Zhang, Xiaomin; Gao, Ya; Chen, Jianmei; Zhou, Anwei; Lu, Qiangbing; Wang, Zeyu; Shao, Kaifeng; Wu, Heming; Ning, Xinghai
Abstract: Despite multiple treatment options being available, many critical challenges are still ongoing in the treatment of oral squamous cell carcinoma (OSCC). Particularly, the major hurdle is to avoid facial disfigurement and oral function disability during treatment. Herein, nanoengineered mesenchymal stem cells (MSCs) are developed as a supersonosensitizer, named M/LPV/O2, for improving nondestructive sonodynamic therapy (SDT) against OSCC along with good therapeutic compliance. M/LPV/O2 is composed of an MSCs membrane functionalized liposomal formulation of oxygen‐loading perfluorocarbon and sonosensitizer verteporfin (M/LPV/O2 ), which can not only increase circulation and targeting efficacy but also supply oxygen to overcome tumor‐hypoxia‐associated resistance in SDT, resulting in enhanced therapeutic outcomes in vitro and in vivo. It is identified that M/LPV/O2 effectively stimulates the generation of reactive oxygen species even in hypoxic conditions, and consequently tremendously induces cancer cell death. In addition, M/LPV/O2 displays good tumor accumulation and penetration under ultrasound stimulation, and efficiently induces tumor inhibition and even abrogation, leading to prolonged survival of tumor‐bearing mice. Importantly, M/LPV/O2 ‐based SDT exhibits minimal systemic adverse effects and successfully maintains oral functions with no facial tissue damage. Therefore, these studies provide a promising therapeutic strategy for OSCC, which has a potential to enhance life quality and compliance after treatment. Abstract : Nondestructive sonodynamic therapy (SDT) is developed for the treatment of oral cancer with good compliance. An ultrasound‐responsive mesenchymal stem cells membrane functionalized liposome is designed for co‐delivery of sonosensitizer and oxygen, which not only increases tumor targeting and penetration but also supplies oxygen to enhance SDT effects to eliminate tumors, resulting in prolonged survival and maintenance of oral functions.